World Armaments and Disarmaments / SIPRI Yearbook 1978 - Stockholm International Peace Research Institute (Taylor And Francis Ltd, 1978)
Abreviation and Conventions and Conversions, Developments of the Year, Recent Developments in Armaments and Disarmament, The Nuclear Fuel Cycles and Nuclear Proliferations, The Military on the Human Environment, Military Satellites, The Arms Race in Space, Development in World Armaments, Military Expenditure, World Arms Production, The Trends in the Arms Trade with the Third World, Sources and Methods for the World Armaments Data, Developments in Arms Control and Disarmament, Disarmament and Development, The Comprehansive Test Ban, The Destruction of Chemical Warfare Agents, The Prohibition of New Weapons, Mutual Force Reductions: Status and Prospects, The Strategic Arms Limitation Talks, Developments in Arms Control and Disarmament, Index.